(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study examined the relationship between agility, eye–foot coordination, and layup performance among beginner basketball athletes. A quantitative correlational design was employed involving a sample of novice players selected through purposive sampling. Agility was measured using the Illinois Agility Test, eye–foot coordination was assessed through the Eye–Foot Coordination Test, and layup performance was evaluated using a standardized layup skill assessment. Data were analyzed using Pearson correlation and multiple regression to determine both individual and combined contributions of the variables. The findings revealed a significant positive relationship between agility and layup performance, indicating that athletes with higher agility demonstrated better control, balance, and directional movement during layup execution. Eye–foot coordination also showed a strong and significant correlation with layup performance, suggesting that perceptual–motor integration plays a critical role in timing, rhythm, and accuracy during the layup. Multiple regression results further indicated that both agility and eye–foot coordination collectively contributed significantly to layup performance, with coordination emerging as the stronger predictor. Overall, the study highlights the importance of developing foundational motor skills in beginner basketball athletes. Training programs should integrate agility drills and coordination-based activities to enhance movement efficiency and support the mastery of layup techniques. These findings contribute to the growing body of research on motor abilities and basketball skill performance, providing practical implications for coaches, trainers, and physical education practitioners